A Project Report on Cloud Computing for Agent Based Urban Transportation - BHARAT SURANA, DURGESH PIRTANI, NABIN PRADHAN and SURAJEET GOGOI (2011)
INTERNAL GUIDE : Muthaiah U EXTERNAL GUIDE : Avayambal K USN NO : 1MJ08CS015, 1MJ08CS024, 1MJ08CS049 and 1MJ08CS094 CARRIED OUT AT : Mvj College Of Engineering Bangalore-560067 ACC NO : PR1826
Keywords: Transportation